Linking between Brand Leadership, Customer Satisfaction, and Repurchase Intention in the E-commerce Industry - Novitasari, Dewiana; Napitupulu, Bonar Bangun Jeppri; Abadiyah, Siti; Silitonga, Nelson; Asbari, Masduki (International Journal of Social and Management Studies, 2022)
The purpose of this study is to investigate the effect of brand leadership (which consists of the dimensions of quality, value, innovation, and popularity) perceived by consumers of an e-commerce website on customer satisfaction among private college students. In addition to testing the effect of customer satisfaction on repurchase intention. The sample of this research was taken from 1026 students using simple random sampling techniques and using SEM (Structural Equation Model) with SmartPLS software version 3.0 as a statistical tool. The results of this study indicate that all dimensions of brand leadership have a positive and significant effect on customer satisfaction. Likewise, the customer satisfaction variable has a positive and very significant effect on repurchase intention among respondent students. The quality dimension has the greatest influence on increasing customer satisfaction on e-commerce sites. Then followed by the dimensions of value, innovation, and popularity dimensions.